1987
DOI: 10.1111/j.1476-5381.1987.tb11323.x
|View full text |Cite
|
Sign up to set email alerts
|

[Met5]enkephalin acts via δ‐opioid receptors to inhibit pelvic nerve‐evoked contractions of cat distal colon

Abstract: The effects of opioids on the sacral parasympathetic outflow to cat distal colon were studied in vitro using muscle strips orientated in the axis of the longitudinal muscle layer, with pelvic nerves attached. Electrical stimulation of the pelvic nerves evoked contractions that were blocked by atropine (1 × 10−6 m) and tetrodotoxin (3 × 10−7 m). [d‐Pen2, d‐Pen5]enkephalin and [Met5]‐ and [Leu5]enkephalin caused concentration‐dependent, reversible inhibition of pelvic nerve‐evoked contractions, with IC50 values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…dynorphin A or ,J-endorphin, and several times more potent than DAMGE (McKnight, Corbett, Marcoli & Kosterlitz, 1985;Takemori & Portoghese, 1985;von Kiugelgen, Illes, Wolfe & Starke, 1985;Sheehan, Hayes & Tyers, 1986;Kennedy & Krier, 1987) endorphin and DAMGE in the human colon imply that the actions of LENK and MENK are predominantly or solely mediated by o-opioid receptors. The site of action of LENK and MENK and the synthetic enkephalins is most likely to be prejunctional.…”
Section: Effects Of Enkephalins In the Human Colonmentioning
confidence: 99%
“…dynorphin A or ,J-endorphin, and several times more potent than DAMGE (McKnight, Corbett, Marcoli & Kosterlitz, 1985;Takemori & Portoghese, 1985;von Kiugelgen, Illes, Wolfe & Starke, 1985;Sheehan, Hayes & Tyers, 1986;Kennedy & Krier, 1987) endorphin and DAMGE in the human colon imply that the actions of LENK and MENK are predominantly or solely mediated by o-opioid receptors. The site of action of LENK and MENK and the synthetic enkephalins is most likely to be prejunctional.…”
Section: Effects Of Enkephalins In the Human Colonmentioning
confidence: 99%
“…Effects of naloxone and ICI 174,864 Naloxone (106 M) and ICI 174,864 (10-6 M) (a selective antagonist at 6-opioid receptors (Cotton et al, 1984;Corbett et al, 1984;Kennedy & Krier, 1987a)) had no effect on transmembrane potential or membrane input resistance (n = 5 and n = 3, respectively In the presence of naloxone (10-6 M), the inhibitory actions of DPDPE (3 x 10-6 M-6 M) on fast e.p.s.ps were significantly antagonized (P < 0.05) (Figure 3a) (control =44± 4% inhibition: test 6± 6% inhibition: n = 3 in both cases). This was seen whether naloxone had potentiated fast e.p.s.ps (n = 1) or not (n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study we showed that opioids inhibit pelvic nerve-evoked contractions of cat distal colon longitudinal muscle in vitro (Kennedy & Krier, 1987a). This action was mediated via prejunctional 6-opioid receptors, located, at least in part, on neurones in the colonic myenteric plexus.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations